Strategy Approaches in the Video Game Industry. The Case Study of South Korea, the USA and Poland - Niemczyk, Jerzy; Borowski, Kamil; Nobel, Marek (Podejścia strategiczne w branży gier wideo. Studium przypadku Korei Południowej, Stanów Zjednoczonych i Polski, 2022)
The problem of interested in these studies was to identify the approaches to strategies that dominate the gaming sector in the USA, Korea and Poland. Solving this problem is the main goal of the research, the results of which are presented in this article. The cognitive aim is to broaden the knowledge of approaches to strategy in new sectors, such as gaming, at various stages of its development. The methodological aim is to check the usefulness of the approach and the analysis based on the principle of the so-called “grey intelligence”. The utilitarian aim is to indicate the directions of development of companies in this sector based on the theoretical projections of the strategy. The research was conducted in Q1 2022, and the result is a description of the dominant strategies in the gaming sector. The originality value of this research is to use theoretical approaches to strategy to identify strategies in new sectors and to verify the utility of these approaches.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 1 (63), s. 29-55
Keywords: strategies; strategic analysis; gaming; general management; Video Game Companies; strategie; analiza strategiczna; zarządzanie; sektory gamingowe